2018
DOI: 10.15406/jabb.2018.05.00145
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Punica granatum peel as an eco-friendly biosorbent for the removal of methylene blue dye from aqueous solution

Abstract: Punica granatum peels (PGP) have successfully been employed as a natural nonconventional low-cost adsorbent for the removal of methylene blue (MB) dye from aqueous solution. Fourier Transform Infra-Red analysis was performed to identify the functional groups present in PGP. Surface morphology of PGP before and after adsorption with MB was studied by analyzing micrograph images of Scanning Electron Microscopy (SEM). The equilibrium and kinetic data were analyzed in the light of different available isotherm and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…This main that the balance is carried out without limitations of the formation of the monolayer and surface of nDCPD is highly heterogeneous allowing to have different adsorption heats scattered throughout the s urface making it more efficient to remove the dyes. This result is consistent with the reported in the literature for different bioadsorbent s (Kyzas et al, 2017;Kwak et al, 2018;Guo et al, 2014;Zhang et al, 2019;Uddin & Baig, 2019;Cao et al, 2018;Rahman, Akter, & Abedin, 2013;Do-Nascimiento et al, 2014;Tabrizi & Yavari, 2015;Uyar, Kaygusuz, & Erim, 2016;Li et al, 2016;Zong, Li, Tian, Lin, & Lu, 2018;Mudyawabikwa, Mungondori, Tichagwa, & Katwire, 2017;Cheng et al, 2015;Raval, Shah, & Shah, 2016;Shakoor & Nasar, 2017;Mashkoor & Nasar, 2020b;Bulgariu et al, 2019;Kadhom, Albayati, Alalwan, & Al-Furaiji, 2020), but there are other reports where it is mentioned that the best model are Langmuir and SIPS (Qian, Luo, Wang, Guo, & Li, 2018;Mounia et al, 2018;He et al, 2019;Shakoor & Nasar, 2016;Sun et al, 2019;Ma et al, 2018;Islam, Ahmed, Khanday, Asif, & Hameed, 2017;Yang & Guan, 2018;Lv et al, 2019; Marques In general, both models have been reported as the most suitable for adsorption of dyes and already depends on the criteria used to choose the best. The value of n<1 for all temperatures implies that the adsorption on the surface of the bioadsorbent is a physical and favorable process, this was corroborated by Shakoor and Nasar (2017).…”
Section: Kinetic Models Equationsupporting
confidence: 92%
See 1 more Smart Citation
“…This main that the balance is carried out without limitations of the formation of the monolayer and surface of nDCPD is highly heterogeneous allowing to have different adsorption heats scattered throughout the s urface making it more efficient to remove the dyes. This result is consistent with the reported in the literature for different bioadsorbent s (Kyzas et al, 2017;Kwak et al, 2018;Guo et al, 2014;Zhang et al, 2019;Uddin & Baig, 2019;Cao et al, 2018;Rahman, Akter, & Abedin, 2013;Do-Nascimiento et al, 2014;Tabrizi & Yavari, 2015;Uyar, Kaygusuz, & Erim, 2016;Li et al, 2016;Zong, Li, Tian, Lin, & Lu, 2018;Mudyawabikwa, Mungondori, Tichagwa, & Katwire, 2017;Cheng et al, 2015;Raval, Shah, & Shah, 2016;Shakoor & Nasar, 2017;Mashkoor & Nasar, 2020b;Bulgariu et al, 2019;Kadhom, Albayati, Alalwan, & Al-Furaiji, 2020), but there are other reports where it is mentioned that the best model are Langmuir and SIPS (Qian, Luo, Wang, Guo, & Li, 2018;Mounia et al, 2018;He et al, 2019;Shakoor & Nasar, 2016;Sun et al, 2019;Ma et al, 2018;Islam, Ahmed, Khanday, Asif, & Hameed, 2017;Yang & Guan, 2018;Lv et al, 2019; Marques In general, both models have been reported as the most suitable for adsorption of dyes and already depends on the criteria used to choose the best. The value of n<1 for all temperatures implies that the adsorption on the surface of the bioadsorbent is a physical and favorable process, this was corroborated by Shakoor and Nasar (2017).…”
Section: Kinetic Models Equationsupporting
confidence: 92%
“…The value of n<1 for all temperatures implies that the adsorption on the surface of the bioadsorbent is a physical and favorable process, this was corroborated by Shakoor and Nasar (2017). The value of RL (Table 3) where at any temperature is less than 1 for MO and MB (Hernández-Maldonado et al, 2017;Shakoor & Nasar, 2017;Nogueira et al, 2018). The adsorption capacity obtained for MB were 44.42, 71.71 and 179.81 mg/g at 25, 35 and 45 °C, respectively, where it can be noted that the higher temperature improves the adsorption of nDCPD, this coincides with the energy by absorbate molecular (E) decreases with the temperature increase, which makes it easier to capture the dye and therefore a removal percentage of 97.1 % at 45 °C was achieved.…”
Section: Kinetic Models Equationmentioning
confidence: 84%
“…Generally, various biomass and agricultural wastes are preferred for preparing carbonaceous adsorbents due to its multiple advantages such as renewability, low-cost precursor, and environment friendliness [21]. Biomass materials and agricultural wastes were widely utilized as low-cost biosorbents for the removal of cationic dyes dye such as Citrus limetta peel waste [22], Cucumis sativus peel waste [23], Punica granatum peel [24], sulphuric acid-treated orange peel [25], fallen leaves [26], Tectona grandis sawdust [27], and Luffa aegyptiaca peel [28]. The adsorption capacity and surface property of the adsorbent prepared from biomass depend on the type of chemical activator, and the source of the precursor, in addition to the activation process [29].…”
Section: Introductionmentioning
confidence: 99%
“…Cotton gin rubbish dust 112.6 [82] Corn cob 405.22 [83] Bread nutshell 409.00 [84] Terminalia catappa (Indian almond) husks 88.62 [85] White pine sawdust 87 [86] Soy husk 169.90 [87] Punica granatum bark 10.7296 [88] Brown algae Sargassum muticum 9.55 [89] Rice straw 20.38 [90] Streptomyces fradiae biomass 59.63 [91] Pitaya peels 190.30 [92] Pomegranate peels 200.0 [93] Syringa vulgaris leaf powder 188.2 [94] Weeds 41,67 [95] Cucumis sativus bark 20.1410 [96] Walnut shell powder 142.85 [97] Water…”
Section: Adsorbentmentioning
confidence: 99%